Trends in Margasari Mangrove Forest Health Indicators, East Lampung Regency - Nurfaizi, Mohamad Ilham; Safe'i, Rahmat; Kaskoyo, Hari; Hilmanto, Rudi (P3KM Politeknik Pertanian Negeri Samarinda, 2023)
Mangrove forests are a life-support system and have ecological, socio-cultural, and economic benefits. Monitoring trends in forest health indicators is carried out to control forest damage so that it remains below the loss threshold, thereby ensuring the sustainability of mangrove forests. The margasari mangrove forest is one of the ecosystems in lampung province that acts as a buffer and protector for coastal areas. A healthy forest is one that can carry out its functions in a real way, be they conservation functions, protection functions, or production functions. The margasari mangrove forest is categorized as a protected forest, so it needs to be monitored intensively so that its sustainability is maintained. The aim of the research is to determine trends in health indicators for the margasari mangrove forest in east lampung regency. The research was carried out using the forest health monitoring method, observing each tree in the plot clusters and analyzing ecological indicators including productivity, vitality, and site quality. The research results show that productivity indicators have increased by 1.716 m3/ha S-C and 10.31 m3/ha P-T, CLI has increased by 3.22 S-C and 4.86 C-T, VCR has decreased by 2.05 S-C and 0.01 C-T, and indicators of soil pH experienced a decrease in S-C of 0.002 and an increase in C-T of 0.085. The fluctuations and condition of each indicator are influenced by changes in the condition of the ecological indicators of the mangrove forest and by human activities and natural conditions that threaten the sustainability of the mangrove forest